An iron-sulfur domain of the eukaryotic primase is essential for RNA primer synthesis - Klinge, Sebastian (2007)
Primases synthesise the RNA primers that are necessary for replication of the parental DNA strands. Here we report that the heterodimeric archaeal/eukaryotic primase is an iron-sulfur (Fe-S) protein. Binding of the Fe-S cluster is mediated by an evolutionarily conserved domain at the C terminus of the large subunit. We further show that the Fe-S domain is essential to the unique ability of the eukaryotic primase to start DNA replication.